DINAMIKA HUKUM PERWALIAN NIKAH DALAM KONTEKS KEMANDIRIAN PEREMPUAN MUSLIM MILENIAL - Azhari, Azhari (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
The research centered on the tension between traditional marriage guardianship laws, where the guardian holds full authority, and the reality of the independence of millennial Muslim women who have become autonomous and active subjects in making their life choices. This tension creates a gap between formal rules and social practice. This research is designed as library research. In this study, the validity test is focused on credibility through triangulation of sources. The results of the study show that: 1). From Authority to Approval: There has been a paradigm shift in understanding religious texts. The role of the guardian is no longer seen as an absolute authority that must be obeyed, but as a party who gives approval and blessing in a partnership contract. This understanding was born from a reinterpretation that emphasized the principles of voluntariness and equality. 2).. Support system vs. Gatekeeper: In practice, the guardian has two faces. On the one hand, it can be a "gatekeeper" who blocks women's choices on traditional grounds, creating conflict. On the other hand, it can function as a "support system" that provides support and advice. Millennial women are actively negotiating, from dialogue to threats using legal channels, to change the role of guardians from barriers to supporters. 3. Regulation and Reality: Positive law, in this case the Compilation of Islamic Law (KHI), still requires guardians. However, it also provides a way out. Through Article 23 of the KHI, the Religious Court can appoint a substitute guardian if the guardian refuses without sharia reasons. This mechanism became a safety valve that responded to the demands of independence, while the discourse of legal reform to adopt a more egalitarian view continued to emerge.